Analysis on Shift of Nature Modes of Liquid Sloshing in a 3D Tank Subjected to Oblique Horizontal Ground Motions with Damping Devices. (23rd June 2013) - Wu, Chih-Hua; Faltinsen, Odd Magnus; Chen, Bang-Fuh
Abstract : The extended study of Wu et al. (2012) of sloshing fluid in tanks with internal structures from 2D to 3D is presented in the paper. The phenomenon of liquid sloshing in a 3D tank with various damping devices is solved by the time-independent finite difference method combined with the ghost (fictitious) cell approach. Two types of damping devices, a tank bottom-mounted baffle and a vertically surface-piercing plate, are considered in the study. In this work, the experimental measurement of liquid sloshing in a 3D tank with the baffle is carried out to further validate the present simulation. The comparison of the results between the experimental measurement and the present computation shows good accuracy. The effect of the vertically tank bottom-mounted baffle or the vertically surface-piercing plate on various sloshing waves for the tank under horizontal oblique excitation is discussed and investigated. The phenomena of the shift of the nature frequency of the tank with damping devices due to various oblique horizontal excitations under different sloshing waves are presented in detail. The sloshing wave type is varied due to the influence of the baffle or the plate, and the coexistence of two types of sloshing waves is found for the tank under larger excitation frequencies.